2022
DOI: 10.3390/ani12213048
|View full text |Cite
|
Sign up to set email alerts
|

Home Range and Habitat Use of the Swan Goose (Anser cygnoides L. 1758) during Wintering in the Seocheon Tidal Flat, South Korea, Using GPS-Based Telemetry

Abstract: The Seocheon Tidal Flat is an important staging and wintering site for the Far East Russian population of Swan Goose (Anser cygnoides) in the East Asian–Australasian Flyway. However, rapid environmental changes for tourism in this area can threaten the survival of this vulnerable population by hindering sufficient rest and wintering; therefore, establishing protection strategies based on Swan Goose behavioral characteristics is necessary. Here, we estimated Swan Goose core home ranges and habitat use based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, bird movement patterns interact intricately with landscape configuration, with avian inhabitants in fragmented habitats expanding their range to exploit multiple patches to meet their energy needs [8]. Thus, the assessment of avian habitat utilization necessitates a consideration of diverse land types [9]. Previous studies have underscored the influence of landscape elements composition and structure on bird abundance and distribution [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bird movement patterns interact intricately with landscape configuration, with avian inhabitants in fragmented habitats expanding their range to exploit multiple patches to meet their energy needs [8]. Thus, the assessment of avian habitat utilization necessitates a consideration of diverse land types [9]. Previous studies have underscored the influence of landscape elements composition and structure on bird abundance and distribution [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, diurnal and nocturnal disparities in birds' habitat utilization are evident, with daytime activities predominantly centered on foraging and movement, exhibiting variations in activity intensity and range compared to nighttime behaviors [8]. For instance, geese exhibit a preference for foraging or resting in rice fields and intertidal zones during the day, while opting for mudflats for roosting at night [9]. The daytime home range of wintering whooper swans in Sanmenxia surpasses that of the nighttime range, with daytime foraging activities concentrated around Canglong Lake, while nighttime sites are predominantly situated near the wooden walkway at Canglong Lake and the black swan Base at Qinglong Lake [13].…”
Section: Introductionmentioning
confidence: 99%
“…Shorebirds, for example, adjust their foraging strategies based on lighting conditions, using either vision or touch to locate food (Robert and McNeil 1989). Moreover, studies have shown that some waterbirds utilize different habitats during the day and night (Dorr et al 2004, Barbaree et al 2015, Joo and Lee 2022. Geese and ducks, for instance, often rest in low disturbance habitats during the day and move to nearby wetlands for foraging at night (Parejo et al 2019, McDuie et al 2021.…”
Section: Introductionmentioning
confidence: 99%